PENINGKATAN KOMPETENSI GURU DALAM MENYUSUN INSTRUMEN PENILAIAN HASIL BELAJAR MELALUI SUPERVISI AKADEMIK TEKNIK KELOMPOK - Siti Mariyah (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2019)
The purpose of this study was to improve teacher competency in compiling learning outcomes instruments through academic supervision of group techniques at Pundung Elementary School, Imogiri, in 2017/2018 academic year. This study is a school action research conducted in three cycles. Each cycle carried out in two meetings consisted of four steps, namely planning, action, evolution, and reflection. The subjects were 14 elementary school teachers at Pundung, Imogiri, consisting of 10 classroom teachers and 4 subject teachers. The results of the study show that the group technique applied in academic supervision may improve the ability of the teacher in compiling the learning outcomes instruments. The average values of teachers in compiling learning outcomes instruments were increased from cycle I, Cycle II, and Cycle III, i.e. 69, 81 and 88 respectively. The observations on the instruments in Cycle I revealed 4 teachers (28.6%) performed substantial qualification, followed with 13 teachers (92.9%) performed good qualification in Cycle II, and 11 teachers (79%) performed very good qualifications in Cycle III.